Three‐dimensional dynamic contrast‐enhanced MRI for the accurate, extensive quantification of microvascular permeability in atherosclerotic plaques. (30th August 2015) - Calcagno, Claudia; Lobatto, Mark E.; Dyvorne, Hadrien; Robson, Philip M.; Millon, Antoine; Senders, Max L.; Lairez, Olivier; Ramachandran, Sarayu; Coolen, Bram F.; Black, Alexandra; Mulder, Willem J. M.; Fayad, Zahi A.
<x xml:space="preserve">Abstract</x> Atherosclerotic plaques that cause stroke and myocardial infarction are characterized by increased microvascular permeability and inflammation. Dynamic contrast‐enhanced MRI (DCE‐MRI) has been proposed as a method to quantify vessel wall microvascular permeability in vivo. Until now, most DCE‐MRI studies of atherosclerosis have been limited to two‐dimensional (2D) multi‐slice imaging. Although providing the high spatial resolution required to image the arterial vessel wall, these approaches do not allow the quantification of plaque permeability with extensive anatomical coverage, an essential feature when imaging heterogeneous diseases, such as atherosclerosis. To our knowledge, we present the first systematic evaluation of three‐dimensional (3D), high‐resolution, DCE‐MRI for the extensive quantification of plaque permeability along an entire vascular bed, with validation in atherosclerotic rabbits. We compare two acquisitions: 3D turbo field echo (TFE) with motion‐sensitized‐driven equilibrium (MSDE) preparation and 3D turbo spin echo (TSE). We find 3D TFE DCE‐MRI to be superior to 3D TSE DCE‐MRI in terms of temporal stability metrics. Both sequences show good intra‐ and inter‐observer reliability, and significant correlation with ex vivo permeability measurements by Evans Blue near‐infrared fluorescence (NIRF). In addition, we explore the feasibility of using compressed sensing to accelerate 3D DCE‐MRI of atherosclerosis, to improve its temporal resolution and therefore the accuracy of permeability quantification. Using retrospective under‐sampling and reconstructions, we show that compressed sensing alone may allow the acceleration of 3D DCE‐MRI by up to four‐fold. We anticipate that the development of high‐spatial‐resolution 3D DCE‐MRI with prospective compressed sensing acceleration may allow for the more accurate and extensive quantification of atherosclerotic plaque permeability along an entire vascular bed. We foresee that this approach may allow for the comprehensive and accurate evaluation of plaque permeability in patients, and may be a useful tool to assess the therapeutic response to approved and novel drugs for cardiovascular disease. Copyright © 2015 John Wiley & Sons, Ltd.